Pluralism, Constitution, Neutrality. Carl Schmitt’s Remarks at the Langnamverein Assembly in 1930 - Fraile, Nicolás (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
The aim of this article is to examine Carl Schmitt's remarks at the Langnamverein assembly in November 1930 —two years before the popularised lecture "Strong State and Sound Economy" was delivered within the same association— in which it was suggested that all the legal means at the Reich government's disposal should be made use of. To this end, each of the topics that structure his remarks and allow us to understand his political proposal is covered in a separate section: 1) pluralism, 2) constitutional reform, and 3) internal political neutrality. Finally, concluding reflections highlight the contributions and enduring relevance of Schmitt's remarks.
Keywords: State; Statism; Neutral Power; Economy; Partisanship